Expression and structure-function analysis of de, a sperm cysteine rich secretory protein that mediates gamete fusion - Ellerman, Diego Andrés (2002)
Rat sperm epididymal glycoprotein DE belongs to the cysteine- rich secretory protein (CRISP) family and participates in sperm-egg fusion through its binding to complementary sites on the egg surface. To investigate the molecular mechanisms underlying the role of DE in gamete fusion, in the present work we expressed DE in a prokaryotic system, and examined the relevance of carbohydrates and disulfide bonds for the biological activity of the protein. Immunofluorescence and sperm-egg fusion assays carried out in the presence of recombinant DE (recDE) revealed that this protein exhibits the ability to bind to the DE-egg binding sites and to inhibit gamete fusion, as does native DE (nDE). Comparison of the proteins indicated, however, that the inhibitory ability of recDE was significantly lower than that of nDE. This difference would not be due to the lack of carbohydrates in the bacterially expressed protein because enzymatically deglycosylated nDE was as able as the untreated protein to inhibit gamete fusion. To examine whether disulfide bridges are involved in DE activity, the presence of sulfhydryls in nDE and recDE was evaluated by the biotin-maleimide technique. Results indicated that, unlike nDE, in which all cysteines are involved in disulfide bonds, recDE contains free thiol groups. Subsequent experiments showed that reduction of nDE with dithiothreitol significantly decreased the ability of the protein to inhibit gamete fusion. Together, these results indicate that whereas carbohydrates do not have a role in DE-mediated gamete fusion, disulfide bridges are required for full biological activity of the protein. To our knowledge, this is the first study reporting the relevance of structural components for the function of a CRISP member.